The Impact of Antibiotic Resistance in Childhood Campylobacter Infections Before and After the COVID-19 Pandemic in the Southeast Region of Romania - Cristina Chiurtu; Elena Mocanu; Bogdan Florentin Nitu; Ana Maria Iancu; Cristina Maria Mihai; Mara Andreea Cambrea; Raluca Mihai; Mihaela Mavrodin; Anca Daniela Pînzaru; Ramona Mihaela Stoicescu (Antibiotics)
The world has changed forever as a result of the COVID-19 pandemic. Antimicrobial resistance is a primary global health concern that places a significant financial and health burden on nations. Patients with Campylobacter-caused infections were the subject of the retrospective investigation. The data show that children aged 1–6 are the most commonly affected by Campylobacter enteritis. Resistance levels fluctuated over the course of the two periods. Nine isolates were sensitive to macrolides, and only one was responsive to tetracycline, which indicated inadequate sensitivity across all classes throughout the pandemic. This pattern raises serious concerns about the potential impact on public health. Tetracyclines and fluoroquinolones rank highest in terms of bacterial resistance. Regardless of the species, macrolides remain a practical and sufficient treatment for Campylobacter enteritis. Reassurance is still provided by much lower numbers in the post-pandemic period. There is no evidence to support the alarming claims made in the international literature about macrolides in Romania.